A molecular study of synovial chondromatosis. Issue 3 (18th October 2019) - Agaram, Narasimhan P.; Zhang, Lei; Dickson, Brendan C.; Swanson, David; Sung, Yun‐Shao; Panicek, David M.; Hameed, Meera; Healey, John H.; Antonescu, Cristina R.
Abstract: Synovial chondromatosis (SC) is a rare benign cartilaginous neoplasm in which recurrent fibronectin 1 ( FN1 ) and activin receptor 2A ( ACVR2A ) gene rearrangements have been recently reported. Triggered by a case of malignant transformation in SC (synovial chondrosarcoma) showing a novel KMT2A ‐ BCOR gene fusion by targeted RNA sequencing, we sought to evaluate the molecular abnormalities in a cohort of 27 SC cases using a combined methodology of fluorescence in situ hybridization (FISH) and/or targeted RNA sequencing. Results showed that FN1 and /or ACVR2A gene rearrangements were noted in 18 cases (67%), with an FN1‐ACVR2A fusion being confirmed in 15 (56%) cases. Two cases showed only FN1 gene rearrangement, without other abnormalities. A novel FN1‐NFATc2 gene fusion was noted in one case by RNA sequencing. The remaining nine cases showed no abnormalities in FN1 and ACVR2A genes. No additional cases showed BCOR gene alterations. In conclusion, this study confirms that FN1 ‐ ACVR2A fusion is the leading pathogenetic event in SC, at even higher frequency than previously reported. FISH methodology emerges as an appropriate tool in the identification of FN1 and ACVR2A gene abnormalities, which can be used in challenging cases. Further studies are needed to determine the recurrent potential of BCOR abnormalities in this disease.